Law and authority under the guise of the good - Rodriguez-Blanco, Veronica (Law and practical reason., 2014)
The book argues that an understanding of the nature of legal normativity involves an understanding of the nature and structure of practical reason in the context of the law, and advances the idea that legal authority and normativity are intertwined.